Estimating banks' interest rate risk in the banking book: Beyond the drawbacks of the current regulatory framework - Rosa Cocozza; Domenico Curcio; Igor Gianfrancesco (LUISS Guido Carli, Department of Economics and Business, Arcelli Centre for Monetary and Financial Studies, 2015)
Appropriate methodologies to assess interest rate risk contribute to the sound management of a credit institution and, given the systemic nature of this risk, help to pursue global financial stability. The regulatory models to estimate a bank's exposure to interest rate risk in the banking book are based on very coarse assumptions about the scenarios of interest rate changes. Consistent with the logic underlying the Basel Committee treatment, we develop more sophisticated methodologies to measure the sensitivity of a bank's economic value to changes in interest rates. Our methodologies are based on historical and Monte Carlo simulation and can be applied to publicly available data in a manner replicable by those outside the banking institutions. The performance of both regulatory and more sophisticated methodologies is assessed through a backtesting analysis that allows to verify whether and to what extent their results are both consistent with actual bank exposure and adequate from a prudential perspective. Overall, our empirical evidence suggests that the latter perform better than the former. Based on some major drawbacks that we especially observe within a context of low market rates, the regulatory treatment of the interest rate risk in the banking book should not be considered conclusive: further efforts are required to both supervisors and banks in order to improve the current regulatory framework and to set more effective risk management policies, respectively.
Keywords: G21; G28; G32; 330; banks; interest rate risk; regulation; risk management; historical simulation; Monte Carlo simulation